Implementasi Metode Promethee Pada Sistem Pendukung Keputusan Pemilihan Pengajar - Iqbal Faizal Afif; Gama Wisnu Fajarianto; Anang Andrianto (Faculty of Computer Science, University of Jember, 2022)
Tutoring is a process of providing learning assistance to students from elementary school to high school. One of the tutoring institutions in Jember Regency is Griya Belajar Pintar Arrava. Arrava always tries to provide the best services and facilities for its students by providing quality teachers. Qualified teachers can be obtained through a good teacher selection process. However, Arrava's leader, who also serves as a decision maker, always has difficulty in choosing new teachers. Efforts that can be made to overcome these difficulties are by building a decision support system for teacher selection. The decision support system for teacher selection can assist Arrava leaders in selecting qualified teachers by providing applicant recommendations based on the results of system calculations. One method that can be used in the selection of teachers is the Promethee method. Promethee is a method that is able to solve problems in determining the order (priority). Basically the Promethee method compares the scores between alternatives (applicants) based on each criterion, resulting in a more accurate decision. The results of this study indicate that the applicant who is ranked first is Nur Khotimah with a value of 0.362014, the second is Hendra Setiawan with a value of 0.245347, the third is Miftahul Arifin with a value of 0.000833, the fourth is Novi Ekasari with a value of -0.3025, and the fifth is Nurul Azizah with a value of -0.30569.